KEBIJAKAN PEMBERDAYAAN WAKAF UANG DI KABUPATEN TANAH DATAR - Elimartati Elimartati (Institut Agama Islam Negeri Batusangkar, 2017)
This research analyzes the policy of local government and people of Tanah Datar Regency in exploiting its potential, opportunity, human resources and challenges in increasing money waqf empowerment. The research method used was qualitative. The techniques used in collecting empirical data in the field were interviews and documentation. The findings of the research indicate that the guidelines for implementation of waqf and can be used as a foothold in the management and empowerment of money waqf. The potential of empowerment of money waqf in Tanah Datar Regency can be enhanced by strengthening the wakaf regulation in the regions, establishment of business partners, strengthening the quality of human resources with sharia insight, and adequate financial support. Policy can be done by cooperating with various parties, such as local government, syariah financial institutions (LKS), non-governmental organizations (NGOs), companies and others.